Multicultural Education In Islamic Boarding School (A Descriptive Study of Pesantren DDI Mangkoso, South Sulawesi) - Muhaemin Latif (JICSA : Journal of Islamic Civilization in Southeast Asian, 2016)
The main objective of this research was to elaborate how pesantren contend with multicultural education.  Qualitative methods including: interviews, focus group discussion (FGD) and detailed observations of the life of pesantren were used. The researcher also examined the wide range of literatures related to the topic. The research focused on pesantren Mangkoso Barru, Indonesia, representing traditional pesantren in the region of South Sulawesi. The data was collected from the teachers, students, kyai (religious leaders) in this particular pesantren. The findings suggest that pesantren have their own understanding regarding multicultural education. Their understandings were mainly based on the holy Koran without learning from western perspectives. They believe that human beings were created on the basis of difference, so people must appreciate one another.  The differences related to language, race, religion, are a must. These concepts have been implemented in the pesantren curricula. The curricula are very inclusive and more opened to any difference. The pesantren provides different materials which come from different sects, and students.  There is no enforcement from pesantren management to just learn from specific sect.  In addition, expanding networks of pesantren is also inclusive. They have already collaborated with different organizations in relation to development of pesantren management.  Another issue considered was its vision of leadership which is perceived as very open. The leader (kyai) are frequently involved in multicultural campaigns, such as seminars, workshops, and bench markings. They perceive that the progress of pesantren depends strongly on the way the kyai deals with contemporary issues, including multiculturalism.